1997
DOI: 10.1161/01.cir.96.1.267
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Method for the Estimation of Defibrillation Energy Requirements in Humans

Abstract: The nonthoracotomy lead system used in this study demonstrated stability of defibrillation energy requirements at implant and 3-month follow-up. A new technique for the estimation of the defibrillation energy dose-response relationship was derived by using a weighted logistic regression analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Prior experiments have shown that 14% of the transthoracic current is shunted by the lung during transthoracic defibrillation 6 . Newman and colleagues 7 assessed the time-dependent effects with a transvenous defibrillation system and found that the impedance rises during follow-up. At our 2-month follow-up, we noted a 25% decrease in impedance rather than a rise as was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Prior experiments have shown that 14% of the transthoracic current is shunted by the lung during transthoracic defibrillation 6 . Newman and colleagues 7 assessed the time-dependent effects with a transvenous defibrillation system and found that the impedance rises during follow-up. At our 2-month follow-up, we noted a 25% decrease in impedance rather than a rise as was expected.…”
Section: Discussionmentioning
confidence: 99%
“…A high defibrillation energy requirement (over 24 Joules) provides little margin for safety. However, in the absence of any changes in the clinical status of the patient, defibrillation energy requirements with a transvenous lead system are generally stable over a three month period (Newman D et al, 1997). Inappropriate shocks most often occur due to supraventricular tachycardia, self-terminating VT, and sensing artifacts, e.g., myopotentials or T wave oversensing.…”
Section: Pulmonary Cardiovascular and Mechanical Complications Of Immentioning
confidence: 99%